2018
DOI: 10.1055/s-0038-1627446
|View full text |Cite
|
Sign up to set email alerts
|

All-Inside Anterior Cruciate Ligament Reconstruction—A Systematic Review of Techniques, Outcomes, and Complications

Abstract: The all-inside technique (AIT) for anterior cruciate ligament reconstruction (ACLR) is gaining popularity as a more anatomic, less invasive, technique with the potential for more rapid recovery. This systematic review aims to critically assess components of the technique, its safety profile, outcomes, and complications. PUBMED, EMBASE, and MEDLINE were searched for studies discussing primary ACLR using the AIT. Article screening, quality assessment, and data abstraction were completed in duplicate, and a minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 43 publications
6
51
0
2
Order By: Relevance
“…The KT-1000 allows objective evaluation of the anterior cruciate ligament laxity. Measurements we obtained after surgical reconstruction of the ACL (mean 3.1 ± 1.0 mm) were consistent with major studies in the literature [27,30,31]. However, it is difficult to compare our data with the ones reported in the literature: very few works describe the procedure and N force applied during the test.…”
Section: Different Tegner Activity Scale Outcomes For Each Acl Reconssupporting
confidence: 87%
“…The KT-1000 allows objective evaluation of the anterior cruciate ligament laxity. Measurements we obtained after surgical reconstruction of the ACL (mean 3.1 ± 1.0 mm) were consistent with major studies in the literature [27,30,31]. However, it is difficult to compare our data with the ones reported in the literature: very few works describe the procedure and N force applied during the test.…”
Section: Different Tegner Activity Scale Outcomes For Each Acl Reconssupporting
confidence: 87%
“…A previous systematic review by de Sa et al in 2018 had reported a low graft failure rate and ideal clinical improvement using the all-inside ACLR technique. However, the review focused on compiling the reported outcomes from individual studies rather than the comparison between different surgical methods [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the all-inside technique is superior to conventional full tibial tunnel ACLR remains controversial. A previous systematic review reported the satisfactory clinical outcome of allinside ACLR, but few have described its comparison with the full tibial tunnel method (5). The present systematic review and meta-analysis aimed to compare surgical outcomes between all-inside ACLR using suspensory cortical button fixation with full tibial tunnel ACLR with regard to function, knee stability, graft failure, and further bone tunnel widening.…”
Section: Introductionmentioning
confidence: 97%